A STUDY ON THE PLAYS OF GIRISH KARNAD AND VARIOUS SYMBOLS USED IN HIS PLAYS - Kumar Sharma, Dinesh; Kaur, Japneet (International Journal of Psychosocial Rehabilitation, 2024)
GirishRaghunath Karnad is regarded as one of the best dramatists in Indo Anglian literature, and isknown for his adaptability. He is a cultural administrator, translator, critic, director, actor, poet, anddramatist, among other things. Karnad has received widespread appreciation for his complex portrayalof topics in his plays, which examine existential issues and the human condition. Karnad's use of a varietyof dramatic devices adds to the innovative merging of Indian reason with western emotive culture in hisplays. A careful examination of Karnad's emotional devices in his major plays reveals the playwright'selegant realism and inventiveness, and allows the reader to derive new meanings from the texts